A Dark Personality Traits Measurement (Short Dark Triad: SD3-TH) Psychometric Properties Testing of Thai Version - Boonroungrut1, Chinun; Fei, Huang (Journal of Inclusive and Innovative Education, 2019)
The Short Dark Triad (SD3) measurement was developed and referred to the constellation of Machiavellianism, Narcissism and Psychopathy in 2014. It has been cited over 600 articles in behavior sciences, psychology, finances, management and education. SD3 has been translated at least 6 languages; however, not yet translated and tested psychometric proprieties in Thai context. Objective: to study the measurement validity and reliability in Thai version Methodology: Exploratory and confirmatory factor analysis were used to validate the measurement construct with 411 samples Results: SD3-TH contents 15 questions divided into 3 components; 5 questions each. The goodness of fit indices was acceptable with GFI at .91, RMSEA at .065 and CFI at .93. Moreover, Psychopathy shared negative correlation both Agreeableness and Conscientiousness personality types significantly (NEO-FFI). Conclusion and Suggestion: There are 15 questions in SD3-TH; 5 questions each component. The Thai version of SD3 was validated, and could be applied. The future study can specific the group the sample or validate with another related Thai measurement.